Gender aspects in medical publication – the Wiener klinische Wochenschrift - Heckenberg, Andrea; Druml, Christiane (Wiener Klinische Wochenschrift, 2010)
Summary OBJECTIVE: Medicine is a discipline where there are still pronounced gender imbalances. Whereas worldwide about 50% of beginners in medical schools are female, only few of them reach leading positions. Our aim was to analyze how this situation is reflected in a peer-reviewed general medical-scientific journal. METHODS: We screened all papers submitted to the Wiener klinische Wochenschrift – The Middle European Journal of Medicine between January 2001 and September 2009, analyzing the percentage of female first authors of submitted papers and accepted papers, the contribution of female authors depending on the type of article and medical specialty, and the percentage of invited female peer reviewers as well as the quality of their reviews. MAJOR RESULTS: During the period studied, a total of 2507 manuscripts were submitted to Wiener klinische Wochenschrift . 26% of these papers had female first authors, and this proportion increased continuously from 16% in 2001 to 32% in 2007, whereafter it remained constant. The proportion of papers submitted by female first authors was dependent on the medical subspecialty (e.g. 48% female first authors of pediatric papers, 12% female first authors of cardiology papers). There was no difference in the acceptance rate of papers by male and female first authors; however, a somewhat higher rate of papers with female first authors was subject to rapid rejection (21% vs. 16%). Papers with female first authors more often named a different corresponding author than papers with male first authors, and in most of these cases the corresponding author was a man. More than 40% of all submitted original papers, 24% of the review articles, but only 10% of the editorials had female first authors. During the years studied only 5–11% of reviewers were women, despite that the quality of their reviews was generally better than those by men. Among the 21 members of the editorial board only one is a woman. CONCLUSION: Between 2001 and 2007 the percentage of manuscripts submitted to Wiener klinische Wochenschrift by female authors constantly increased and is now around 30%, reaching almost 50% in some specialties such as pediatrics. Nevertheless, there remains a massive gender imbalance in Wiener klinische Wochenschrift : review papers or invited editorials are only rarely authored by female researchers, a very low percentage of peer reviewers is female – although the quality of their reviews is generally better – and only one member of the editorial board is female. Even though this is mostly a reflection of the general situation in academic medicine, medical journals can and must take action and contribute to the elimination of these gender inequalities.